2012
DOI: 10.1371/journal.pone.0041856
|View full text |Cite
|
Sign up to set email alerts
|

Does Mutualism Drive the Invasion of Two Alien Species? The Case of Solenopsis invicta and Phenacoccus solenopsis

Abstract: Although mutualism between ants and honeydew-producing hemipterans has been extensively recognized in ecosystem biology, however few attempts to test the hypothesis that mutualism between two alien species leads to the facilitation of the invasion process. To address this problem, we focus on the conditional mutualism between S. invicta and P. solenopsis by field investigations and indoor experiments. In the laboratory, ant colony growth increased significantly whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 48 publications
1
46
0
1
Order By: Relevance
“…The species involved in this system have been found tending other hemipterans, i.e., B. osbcurior tending Dalbulus quinquenotatus Delong & Nault (Cicadellidae) (Larsen et al. 1991), B. patagonicus tending Aphis gossypii Glover (Aphididae) (Barnum 2008), P. megacephala tending Coccus viridis (Coccidae) (Reimer et al 1993), and S. invicta tending Phenacoccus solenopsis Tinsley (Pseudococcidae) (Zhou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The species involved in this system have been found tending other hemipterans, i.e., B. osbcurior tending Dalbulus quinquenotatus Delong & Nault (Cicadellidae) (Larsen et al. 1991), B. patagonicus tending Aphis gossypii Glover (Aphididae) (Barnum 2008), P. megacephala tending Coccus viridis (Coccidae) (Reimer et al 1993), and S. invicta tending Phenacoccus solenopsis Tinsley (Pseudococcidae) (Zhou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous9studies have demonstrated that ant workers foraging foliar is significantly enhanced on the P. solenopsis infested cotton plant (Zhou et al. ). Ant colony growth and ant worker survival were significantly improved when ants had access to P. solenopsis (Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids exhibit enhanced feeding and excretion rates when they are attended by ants (Banks & Nixon 1958;Mittler 1958;Takeda et al 1982). Ant tending can even increase the reproductive period and shorten the developmental period of hemipterans (Stadler & Dixon 1999;Zhou et al 2012a). Several studies have indicated that the quality and quantity of the honeydew produced by hemipterans play an important role in the stability and outcomes of hemipteran-ant interactions (Addicott 1978;Sakata 1995;V€ olkl et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In a bad infestation, their honeydew induces the development of sooty mold fungus (Saeed et al, 2007). This species has been recognized as an aggressively invasive species of agricultural and ornamental plants in China. P. solenopsis in the fields is difficult to manage (Ram and Saini, 2010;Vennila et al, 2010;Huang J et al, 2012;Zhou et al, 2012) for the following reasons: 1) this species possesses a waxy coating that protects it from insecticides and natural mortality factors, 2) P. solenopsis can also hide in soil cracks and crevices, 3) P. solenopsis exhibits a high reproductive rate and produces serious overlapping generations, and 4) the higher foraging tempo of ants provides additional effective protection for P. solenopsis. P. solenopsis cannot be controlled effectively; the losses in cotton yield in 2008 or 2009 were 1.4 × 10 6 t in China, 1.12 × 10 6 t in India, and 0.48 × 10 6 t in Pakistan (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%